Equivalent SARS-CoV-2 viral loads by PCR between nasopharyngeal swab and saliva in symptomatic patients - Isao Yokota; Takeshi Hattori; Peter Y. Shane; Satoshi Konno; Atsushi Nagasaka; Kimihiro Takeyabu; Shinichi Fujisawa; Mutsumi Nishida; Takanori Teshima (Scientific Reports, 2021)
Abstract Emerging evidences have shown the utility of saliva for the detection of SARS-CoV-2 by PCR as alternative to nasopharyngeal swab (NPS). However, conflicting results have been reported regarding viral loads between NPS and saliva. We conducted a study to compare the viral loads between NPS and saliva in 42 COVID-19 patients. Viral loads were estimated by the cycle threshold (Ct) values. SARS-CoV-2 was detected in 34 (81%) using NPS with median Ct value of 27.4, and 38 (90%) using saliva with median Ct value of 28.9 (P = 0.79). Kendall’s W was 0.82, showing a high degree of agreement, indicating equivalent viral loads in NPS and saliva. After symptom onset, the Ct values of both NPS and saliva continued to increase over time, with no substantial difference. Self-collected saliva has a detection sensitivity comparable to that of NPS and is a useful diagnostic tool with mitigating uncomfortable process and the risk of aerosol transmission to healthcare workers.